A good response to anti-PD-1 monoclonal antibody plus SBRT in a patient with PD-L1-negative recurrent advanced esophageal cancer: a long-term follow-up case report of a possible abscopal effect - Hai, Tao; Liu, Jia; Lai, Jialu; Zhou, Lin (Frontiers in Oncology, 2024)
There are limited treatment options for recurrent advanced esophageal squamous cell carcinoma. A good response with a possible abscopal effect was observed in a patient with programmed death-ligand 1 (PD-L1)-negative recurrent advanced esophageal squamous cell carcinoma treated with an anti-PD-1 monoclonal antibody plus stereotactic body radiotherapy (SBRT). A 66-year-old male patient was diagnosed with recurrent advanced esophageal squamous cell carcinoma with multiple lung metastases (13 metastatic nodules in total) four months after completing radical radiotherapy plus concurrent and consolidated chemotherapy, and PD-L1 expression in the primary esophageal tumor was negative. This patient received 25 cycles of camrelizumab (an anti-PD-1 monoclonal antibody) in total plus upfront SBRT for two metastatic nodules, which was administered after the first cycle of camrelizumab. After this combined treatment, for most nontarget nodules, an obvious volume decrease and fuzzy change were observed, including two nodules that completely vanished. At the end of follow-up, the progression-free survival and duration of response of this patient were 34 months and 32 months, respectively. This case report indicated that an anti-PD-1 monoclonal antibody combined with SBRT was a promising therapeutic strategy for recurrent esophageal squamous cell carcinoma even in patients with negative PD-L1 expression.